PENGARUH ONLINE CUSTOMER REVIEW, E-SERVICE QUALITY, DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA MELALUI TOKOPEDIA - Fatana Suastrini; Muhammad Helmy Reza (Nusantara Hasana Journal, 2026)
This study aims to determine the influence of online customer reviews, e-service quality, and trust on students' purchasing decisions on Tokopedia. This study used a quantitative method with a questionnaire as the data collection technique. The sample used was 100 student respondents at the State Islamic University of Mataram using a purposive sampling technique. The analytical method used to prove the research hypothesis was Structural Equation Modeling (SEM). The results showed that online customer reviews, e-service quality, and trust had a positive and significant influence on students' purchasing decisions on Tokopedia.